1982
DOI: 10.1115/1.3266330
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Two-Phase Flow Solar Collectors With Application to Heat Pumps

Abstract: A thermodynamic model is developed to analyze the thermal performance of two-phase solar collectors. The well-known equilibrium homogeneous theory is used to model the two-phase flow in the solar collectors. The resultant set of coupled ordinary differential equations for saturated pressure and quality of working fluid in the collector tubes are solved by an iterative procedure using a fourth-order Runge-Kutta method. The results are then applied to determine the thermal performance of a solar assisted heat pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…The concept of DX-samp was first considered by Sporn and Ambrose (1955) in West Virginia. Following the same line work, many theoretical and experimental studies have been reported (Chaturvedi et al, 1982;Morgan, 1982;O'Dell et al, 1984;Chaturvedi and James Shen, 1984;Chaturvedi and Abazeri, 1987;Morrison, 1994;Chaturvedi et al, 1998;Axaopoulos et al, 1998;Hawlader et al, 2001;Huang and Chyng, 2001). A review on such field of work has indicated that the COP values of the DX-SAHP systems range from 2 to 9 and the collector efficiencies vary between 40 and 75% under different climatic conditions, experimentally.…”
Section: Introductionmentioning
confidence: 91%
“…The concept of DX-samp was first considered by Sporn and Ambrose (1955) in West Virginia. Following the same line work, many theoretical and experimental studies have been reported (Chaturvedi et al, 1982;Morgan, 1982;O'Dell et al, 1984;Chaturvedi and James Shen, 1984;Chaturvedi and Abazeri, 1987;Morrison, 1994;Chaturvedi et al, 1998;Axaopoulos et al, 1998;Hawlader et al, 2001;Huang and Chyng, 2001). A review on such field of work has indicated that the COP values of the DX-SAHP systems range from 2 to 9 and the collector efficiencies vary between 40 and 75% under different climatic conditions, experimentally.…”
Section: Introductionmentioning
confidence: 91%
“…Based on our review, in 1980, Chaturvedi et al [3] were possibly the first ones to set out a comprehensive model describing a two-phase flow solar collector with application to heat pumps; they found that a large pressure drop might occur if the refrigerant is passed through a small number of parallel serpentine tube panels. The results suggested that a high COP and collector efficiency are feasible with bare collectors and that a higher collector area improves COP and additionally reduces the electrical energy input, however, reducing the efficiency of said collector due to a higher energy availability, hence, a higher collector temperature that results in higher back losses.…”
Section: Analysis Of the Solar Collectorsmentioning
confidence: 99%
“…However, an inverter compressor is able to make an SAHP system operate under a better condition by changing the frequency of the system as the solar radiation differs. Through a full-year forecast of SAHP system that applied an inverter compressor, researchers like Chaturvedi suggest that not only the COP of a heat pump and thermal efficiency of its collectors, but also the system premium operating performance can be guaranteed by converting the frequency of the compressor to an optimal performance according to weather status in different seasons throughout the whole year [1]. Targeting better heat pump performance and collector efficiencies, temperature of collectors should be 5~10˝C higher than environment temperature [2].…”
Section: Introductionmentioning
confidence: 99%